Presence of Open Science Skills in Learning Outcomes at the Lis Study Programs in Croatia - Džoić, Zrinka; Grzunov, Laura (Central European Journal of Educational Research, 2022)
Open science is an ever-evolving phenomenon. Open science deals with the availability of data and publications, which includes an open approach with which publicly funded research is sought to be made available to all members of society and the public. It is an umbrella term that includes a multitude of assumptions about the future of knowledge creation and dissemination (Fecher & Friesike, 2014). The Organization for Economic Co-operation and Development (OECD) emphasizes libraries as a key player and fundamental drivers of open science because they have adapted their role to today’s age and are now active in preserving, publishing, and disseminating digital scientific material in the form of publications, data, and other research-relate content. During their studies, LIS (Library and information science(s)) students acquire knowledge and develop a set of skills that will prepare them for work in today’s information environment. In 2020. LIBER’s (Ligue des Bibliothèques Européennes de Recherche – Association of European Research Libraries) Digital Skills for Library Staff and Researchers Working Group published a visual presentation of the necessary competencies for librarians and researchers. Information science studies, including those in Croatia, are exposed to constant changes in the field, including the development of open science. For this reason, it is necessary to constantly think about the adaptation of study programs through which students will acquire basic knowledge related to the promotion and advocacy of open science. The term “open science”, and everything it encompasses, should be an integral part of study programs in the field of information sciences. The aim of this paper is to explore the representation of skills and competencies for open science in study programs at the LIS studies in Croatia: Department of Information and Communication Sciences (Zagreb), Department of information sciences (Osijek) and Department of information science (Zadar). This research indicated the need for greater inclusion of the concepts of scientific communication and open science in the learning outcomes at the level of programs in the study of information sciences in Zadar, Zagreb, and Osijek.